A scoping review on the nature and impact of gender based violence on women primary producers - Cathy O'Mullan; Saba Sinai; Sabitra Kaphle (BMC, 2024)
Abstract Background Women in low- and middle-income countries (LMICs) are primary producers of subsistence food and significant contributors to the agricultural economy. Gender Based Violence (GBV) adversely impacts their capacity to contribute and sustain their families and undermines social, economic, and human capital. Addressing GBV, therefore, is critical to creating safe and inclusive environments for women as primary producers to participate fully in rural communities. The aim of this scoping review is to explore the existing evidence on GBV in the context of women primary producers in LMICs to inform research gaps and priorities. Methods A scoping review was conducted using PubMed, Web of Science, Ebscohost and Google Scholar using keywords related to GBV and women producers in LMICs. Peer-reviewed journal articles published between January 2012 and June 2022 were included in the review. Duplicates were removed, titles and abstracts were screened, and characteristics and main results of included studies were recorded in a data charting form. A total of 579 records were identified, of which 49 studies were eligible for inclusion in this study. Results Five major themes were identified from our analysis: (1) extent and nature of GBV, (2) the impact of GBV on agricultural/primary production livelihood activities, (3) sociocultural beliefs, practices, and attitudes, (4) aggravating or protective factors, and (5) GBV interventions. Addressing GBV in agriculture requires inclusive research approaches and targeted interventions to empower women producers, promote gender equality, enhance agricultural productivity, and contribute to broader societal development. Despite attempts by researchers to delve into this issue, the pervasive under-reporting of GBV remains a challenge. The true extent and nature of GBV perpetrated against women is far from fully understood in this context. Conclusion Despite the significant challenges posed by GBV to the health, economy and livelihoods of women primary producers in LMICs, there is a paucity in the current state of knowledge. To make meaningful progress, more research is required to understand the relationship between GBV and agricultural settings, and to gain nuanced insight into the nature and impact of GBV on women primary producers in different regions and contexts.